(untitled) (Eurasian Medical Research Periodical, 2026)
Autoimmune thyroid diseases (AITD), primarily comprising Hashimoto’s thyroiditis (HT) and Graves’ disease (GD), represent the most prevalent group of autoimmune disorders globally, affecting approximately 5% of the general population (Hu et al., 2022). The pathogenesis of AITD involves a complex interplay between genetic susceptibility, environmental triggers, and immune dysregulation, leading to the production of thyroidspecific autoantibodies such as anti-thyroid peroxidase (TPOAb) and anti-thyroglobulin (TgAb). Over the last decade, epidemiological shifts have been observed, with a steady increase in the incidence of AITD in both iodine-sufficient and formerly iodine-deficient regions. While the implementation of Universal Salt Iodization (USI) programs has been a cornerstone of global public health, reducing the prevalence of endemic goiter, it has paradoxically been associated with a rise in thyroid autoimmunity (Botello et al., 2020). This phenomenon necessitates a transition in public health focus: from basic iodine deficiency to the more nuanced management of chronic autoimmune inflammation.